2020
DOI: 10.1097/prs.0000000000006520
|View full text |Cite
|
Sign up to set email alerts
|

Regional Patterns of Fluid and Fat Accumulation in Patients with Lower Extremity Lymphedema Using Magnetic Resonance Angiography

Abstract: Background: Fat accumulation is frequently observed in patients with lymphedema but is not accounted for in existing staging systems. Additionally, the specific regional patterns of fat and fluid accumulation remain unknown and might affect outcomes following medical or surgical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
(20 reference statements)
1
25
0
Order By: Relevance
“…This is in stark contrast to the generally accepted dogma that lymphedema is initially comprised of a fluid component, that over time is replaced by fat. Yet, similar descriptive studies carried out by Dayan et al and Brorson et al support our findings [ 7 , 14 ]. Remarkably, we found that patients with BCRL in their dominant arm had 13 percentage points more excess lymphedema volume (dominated by excess lean mass).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in stark contrast to the generally accepted dogma that lymphedema is initially comprised of a fluid component, that over time is replaced by fat. Yet, similar descriptive studies carried out by Dayan et al and Brorson et al support our findings [ 7 , 14 ]. Remarkably, we found that patients with BCRL in their dominant arm had 13 percentage points more excess lymphedema volume (dominated by excess lean mass).…”
Section: Discussionsupporting
confidence: 93%
“…However, the apparent benefit in this study setting of DEXA over magnetic resonance angiography is that magnetic resonance angiography relies on manual and qualitative assessments. In contrast, DEXA scans provide an exact quantitative measure of each tissue component, which is not currently feasible using magnetic resonance angiography [ 14 , 36 ]. Bioimpedance spectroscopy is increasingly being used for evaluating BCRL due to its quick, simple, and noninvasive design [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, on LE CTV images, the lymphedematous limbs of patients taking mTOR inhibitors showed peculiar trabecular areas with honeycomb patterns in the subcutaneous fat, signifying fluid and fibrotic tissue surrounding the adipose tissue accumulation. 30,31 LE CTV images demonstrate the alteration in epidermal and subcutaneous tissue. 32 By measuring the muscular, subcutaneous fat, and total mid-thigh CSA, we analyzed not only qualitative but also quantitative LE CTV findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MRA not only enables us to diagnose lymphedema, it also gives information regarding the distribution of fluid and/or fibrofatty tissue in the limb, as well as information regarding vascular status and possible venous stenosis. A recent study by Dayan et al [ 14 ] shows the impact that MRA can have on the treatment of lymphedema patients. In this study, they examine the MRA results in patients with either primary or secondary lower extremity lymphedema, and subjectively classify and grade the fluid or fat distribution in the limb.…”
Section: Imaging Techniquesmentioning
confidence: 99%